2013
DOI: 10.1186/1748-717x-8-279
|View full text |Cite
|
Sign up to set email alerts
|

CBCT-based volumetric and dosimetric variation evaluation of volumetric modulated arc radiotherapy in the treatment of nasopharyngeal cancer patients

Abstract: ObjectiveTo investigate the anatomic and dosimetric variations of volumetric modulated arc therapy (VMAT) in the treatment of nasopharyngeal cancer (NPC) patients based on weekly cone beam CT (CBCT).Materials and methodsTen NPC patients treated by VMAT with weekly CBCT for setup corrections were reviewed retrospectively. Deformed volumes of targets and organs at risk (OARs) in the CBCT were compared with those in the planning CT. Delivered doses were recalculated based on weekly CBCT and compared with the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…Using weekly CT, Robar et al [18] showed that the mean volume of lPG and rPG decreased by 4.4% and 5.0% per week during a 6-week treatment course. Han et al [19] and Lee et al [20] observed a mean and median relative PGs loss rate of 1.1% and 0.7% per treatment day based on used daily megavoltage CT. Jin et al [21] discovered that the left and right part of the PGs underwent a mean volume reduction of 4.4% and 4.7% per week based on weekly CBCT of ten NPC patients treated with IMRT, and the result was in agreement with the findings in Robar et al [18] and ours. All these researches suggested that the OARs have considerable anatomical changes over the treatment course in H & N patients.…”
Section: Discussionsupporting
confidence: 82%
“…Using weekly CT, Robar et al [18] showed that the mean volume of lPG and rPG decreased by 4.4% and 5.0% per week during a 6-week treatment course. Han et al [19] and Lee et al [20] observed a mean and median relative PGs loss rate of 1.1% and 0.7% per treatment day based on used daily megavoltage CT. Jin et al [21] discovered that the left and right part of the PGs underwent a mean volume reduction of 4.4% and 4.7% per week based on weekly CBCT of ten NPC patients treated with IMRT, and the result was in agreement with the findings in Robar et al [18] and ours. All these researches suggested that the OARs have considerable anatomical changes over the treatment course in H & N patients.…”
Section: Discussionsupporting
confidence: 82%
“…A large dose gradient always exists between the tumour site and the critical structure in VMAT plans, and so volumetric changes, as mentioned previously, create a potential change in the dose received on the critical structure. Jin et al studied the usefulness of the CBCT images-based VMAT plan adaptation in nasopharyngeal tumour patients and found that there was a reduction of 4.5 cm 3 in parotid volume during the course of treatment and, as a result, the dose received was increased up to 8.8% than the planned value [24]. CBCT can be used to monitor such changes on a daily basis and reconstruct the dose apart from providing actual set up information of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Daha önceki çalışmalarda da gösterildiği gibi akciğer olgularında, CBCT tedavi süresine yaklaşık üç dakika eklmesine rağmen ve toplam tedavi dozuna katkısı kV-kV görüntülemeye göre daha fazla olsa da hedef hacmin fraksiyonlar arası lokalizasyonunu belirmede ve set-up sapmalarını azaltmada 2B görüntülemelere göre daha üstün olduğu sonucuna varıldı. [8,22,32,33] İstatiksel olarak araştırıldığında baş boyun hastalarında set-up hatalarını belirlemede kV-kV ve kV CBCT için anlamlı farklılık bulunmaz iken akciğer hastalarında iki görüntüleme arasındaki (p<0.05) fark anlamlı bulunmuştur. Bu nedenle akciğer hastalarında IGRT protokollerinde kV CBCT ve online düzeltme protokolü kullanıldı-ğında PTV oluşturmak için CTV'ye verilecek marj küçülecek ve PTV hacmi daha küçük olacağından kritik organ koruması daha iyi olacaktır.…”
Section: Discussionunclassified